R Object-oriented Programming - Black, Kelly (Birmingham : Packt Publishing, 2014)
Chapter 5: Character and String Operations; Basic string operations; Six focused tasks; Determine the length of a string; Location of a substring; Extracting or changing a substring; Transform case; Splitting strings; Creating formatted strings; Regular expressions; Summary; Chapter 6: Converting and Defining Time Variables; Introduction and assumptions; Converting strings to time data types; Converting time data types to strings; Operations on time data types; Summary; Chapter 7: Basic Programming; Conditional execution; Loop constructs; for loops; while loops; repeat loops
This book is designed for people with some experience in basic programming practices. It is also assumed that they have some basic experience using R and are familiar using the command line in an R environment. Our primary goal is to raise a beginner to a more advanced level to make him/her more comfortable creating programs and extending R to solve common problems.
The assignment classesThe NumericGrade class; The LetterGrade class; Example -- reading grades from a file; Defining indexing operations; Redefining existing functions; Redefining arithmetic operations; Summary; Chapter 11: Case Study -- Simulation; The simulation classes; The Monte-Carlo class; Examples; Summary; Appendix: Package Management; Index
Description based upon print version of record.
Keywords: COMPUTERS / Programming / Open Source; COMPUTERS / Software Development & Engineering / General; COMPUTERS / Software Development & Engineering / Tools; Computer science; Database management; Object-oriented programming (Computer science).; Object-oriented programming (Computer science); R (Computer program language); Electronic books